Electrodeposition of reduced graphene oxide onto gold electrodes: creating thin electrochemically active and optically transparent overlayers. (1st October 2019) - Li, Yan; Martens, Isaac; Cheung, Karen C.; Bizzotto, Dan
Abstract: The electrochemical reduction of graphene oxide (ERGO) into contiguous ultrathin ERGO coatings is presented. Monolayer flakes of graphene oxide are electrochemically reduced onto gold microelectrodes. Electrochemical exfoliation allows convenient removal of the outer layers of the deposited film, (e.g., partially reduced or physically adsorbed flakes) leaving behind a thin layer (∼10 nm) of the ERGO deposit. Raman spectroscopy indicates this process creates a ERGO layer that is characteristic of reduced GO as prepared by other methods. The effectiveness of the ERGO coating as a conductive overlayer was examined using copper underpotential deposition. The ERGO modification was found to be complete and robust covering the electrode surface, with little evidence of exposed gold substrate. Furthermore, simple electrochemical Cu deposition studies confirm that the ERGO overlayers are conductive and electrochemically active and behaviour as expected for a carbon electrode. In addition, these ERGO modified gold surfaces are almost as reflective as the underlying gold substrate showing that the ERGO modification is essentially transparent in the visible wavelength range. Graphical abstract: Image 1